The Impact Of Teachers' Psychological Stress On Work Performance And Early Retirement Intentions: Social Support As A Moderator - Chong, Yee Joan (2014)
The study was undertaken to identify the levels of stress, anxiety and depression among teachers teaching in Sekolah Kluster. The study used Depression Anxiety Stress Scale (DASS) to measure the levels of teachers’ psychological stress. In addition, this study examined the relationship between irrational beliefs, organisational factors and stakeholder expectation and the impact of psychological stress on work performance (absenteeism and presenteeism) and early retirement intentions among teachers. Social support as moderator was introduced in the current theoretical framework to see the effects of the relationship between independent variables and psychological stress. This study added anxiety and depression to measure teachers’ psychological stress as previous studies were mostly focusing on stress. Its objective was to provide in depth understanding of teachers’ psychological stress and its causes and outcomes. Several hypothesised relationships were tested on the data collected by means of questionnaire from a sample of 296 teachers from selected Sekolah Kluster in Peninsular Malaysia. Interaction effects between the independent variables and psychological stress were also tested.